Cerebrospinal Fluid and Blood Lactate and Procalcitonin for Diagnosis of Post-neurosurgical Bacterial Meningitis - Panpruet, Pongpat; Chonhenchob, Areeporn (Asian Journal of Neurosurgery, 2025)
To investigate the diagnostic value of lactate and procalcitonin levels in cerebrospinal fluid (CSF) and blood for the diagnosis of post-neurosurgical bacterial meningitis (PNBM).A 2-year prospective study was conducted at the Faculty of Medicine, Vajira Hospital, Bangkok, Thailand. Data were collected on patient demographics, underlying disease, time to suspected PNBM, operative time, preoperative antibiotic use, blood lactate and procalcitonin levels, and CSF cell count, cell differentiation, protein, glucose, lactate, and procalcitonin levels. Sensitivity, specificity, accuracy, positive predictive value, and negative predictive value were calculated using Fisher's exact test.A CSF lactate level greater than 4 mmol/L showed a sensitivity of 82.2%, specificity of 62.5%, positive predictive value of 92.5%, negative predictive value of 38.5%, and accuracy of 39.62%. A CSF procalcitonin level greater than 0.075 ng/mL showed a sensitivity of 100%, specificity of 0%, positive predictive value of 100%, negative predictive value of 0%, and accuracy of 100%. A blood lactate level greater than 2 mmol/L showed a sensitivity of 17.8%, specificity of 100%, positive predictive value of 100%, negative predictive value of 17.8%, and accuracy of 43.24%. A blood procalcitonin level greater than 0.25 ng/mL showed a sensitivity of 40%, specificity of 50%, positive predictive value of 81.8%, negative predictive value of 12.9%, and accuracy of 44.23%. CSF lactate >5.25 mmol/L had a specificity of 100%, and CSF/blood lactate ratio >7.07 had a specificity of 100% for PNBM diagnosis.CSF lactate and the CSF/blood lactate ratio are useful in the diagnosis of PNBM. However, CSF procalcitonin, blood lactate, blood procalcitonin, and the CSF/blood procalcitonin ratio are not reliable for diagnosing PNBM. CSF lactate greater than 5.25 mmol/L and CSF/blood lactate ratio greater than 7.07 are highly specific for the diagnosis of PNBM.
Keywords: meningitis; cerebrospinal fluid; lactate; procalcitonin; neurosurgical procedures